Mobilitas tamatan madrasah negeri dan pendidikan guru agama negeri di Kalimantan Selatan : laporan hasil penelitian - Mochrani (Balai Penelitian Agama dan Kemasyarakatan, 1985)
Social and economic mobility of graduates of state Islamic religious schools and state teacher training institutions in Kalimantan Selatan.